Are some fund managers better than others? Manager characteristics and fund performance - L. B. Friis; E. V.D.M. Smit (South African Journal of Business Management, 2004)
The research objective has been to find out whether fund manager characteristics help explain fund performance and propensity to risk taking. Eight independent variables; manager age, tenure of the manager with the fund, years of education, whether the manager holds a MBA or CA/CFA qualification, management team size, fund age and fund objective are regressed on measures of fund performance and riskiness.The findings of the study are highly significant and show that fund performance and riskiness are impacted upon by managers' qualifications. One can expect better risk-adjusted performance from a fund manager who holds a CA/CFA qualification. Results show that these managers outperform managers without these qualifications, while taking on less risk than managers with MBA qualifications.
Keywords: 650